Miniature drone antenna design for the detection of airliners. Issue 1 (14th February 2021) - Sidibe, Alassane; Loubet, Gaël; Takacs, Alexandru; Ferré, Guillaume; Ghiotto, Anthony
Abstract: In this paper, the design of a miniature antenna dedicated to the detection of airliners through the demodulation of Automatic Dependence Surveillance-Broadcast system (ADS-B) signals is presented. This antenna is designed for being embedded on the top of a drone in order to detect and avoid collisions with airliners. This antenna consists of an array of Planar Inverted-F Antennas, a quadrature feed network (FN) and a reflector plane (RP). The FN is designed to have output signals with the same amplitude and a 90° phase difference between each other. It achieves circular polarization and maintains the axial ratio of the antenna under −3 dB at the desired frequency (1.09 GHz). The antenna with the FN was manufactured and characterized. It weighs approximately 145 kg with its RP. The measured gain of the proposed antenna is about +3.7 dBi. To validate the design, the manufactured antenna was tested with a Universal Software Radio Peripheral for the processing of ADS-B signals at the French National Microwaves Days 2019 (JNM) student contest. The detection of airliners can reach up to 437 km.